Comparison of Platelet-Lymphocyte Ratio Before and After Chemotherapy in Nasopharyngeal Carcinoma Based on Histopathology - Aksmitayani Aksmitayani; Abdul Kadir; Muhammad Fajar Perkasa; Abdul Punagi (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: Nasopharyngeal carcinoma (NPC) is a non-lymphomatous squamous cell carcinoma in the nasopharyngeal epithelial layer which can be classified into three categories with different prognosis based on histopathological examination. This study aimed to compare platelet-lymphocyte ratio (PLR) in NPC patients before and after chemotherapy based on histopathological type. Method: this cohort study recorded data from medical records. The histopathological type, chemotherapy regimen, clinical stage, and PLR of NPC patients were recorded and compared before and after therapy using paired T-test and Wilcoxon test. The prognostic strength of PLR and the value of the cut-off point was determined by looking at the Area Under Curve (AUC) value using the Receiver Operating Characteristic (ROC) curve method. Results: A total of 44 NPC patients received chemotherapy for three cycles, including 21 patients with NPC type-2 and 23 patients with NPC type-3. There were significant differences in the average PLR before and after undergoing three cycles of chemotherapy in type III NPC (p=0.023). At the same time, there were no statistically significant differences in type-II NPC (p=0.131). The prognostic ability of pre-chemotherapy PLR in assessing disease progression in type II NPC was good (AUC=0.763) with 100.0% sensitivity and 73.68% specificity. In type III NPC, the prognostic ability of PLR was very good (AUC 0.881) with 100% sensitivity value and 76.19% specificity. Conclusion: A significant PLR decrease was obtained after the 3rd cycle of chemotherapy in type III NPC following brexel-cisplatin regimen but not in type II NPC. This is probably due to the use of a cisplatin therapy regimen that is more responsive to type III NPC. In addition, examining PLR value before undergoing chemotherapy can be a predictor in assessing disease progression in type III NPC patients.